Consider `f:R - {-4/3} -> R - {4/3}` given by f(x) = `(4x + 3)/(3x + 4)`. Show that f is bijective. Find the inverse of f and hence find `f^(-1) (0)` and X such that `f^(-1) (x) = 2`

Advertisement Remove all ads

#### Solution

f(x) = `(4x + 3)/(3x + 4)`

Assume its not one – one

∴ x_{1} and x_{2} belonging to domain such that `f(x_1) = f(x_2)`

for every ‘y’ there is a x .

∴ it is onto

Concept: Inverse of a Function

Is there an error in this question or solution?

Advertisement Remove all ads